A thousand hystero-Tubal hidrotubaciones in sterile - Ascenzo Cabello, Jorge (2015)
We conducted 1,070 hísteros-tubal hidrotubaciones in 146 patients who had committed the tubal factor, which gives an average of 7.3 per patient hidrotubaciones. One hundred and sixteen cases - 79.4 percent - were frank obstruction. Thirty cases - 20.5 percent - had a proven stenosis. Persuflaciones hysterosalpingography and two - the second with antispasmodic - prior to hidrotubaciones are indispensable to a firm diagnosis of tubal commitment. Hidrotubaciones practice two cycles, each of five applications, ie ten hidrotubaciones for two months. They are held every forty-eight hours, starting them in the seventh or eighth day of the cycle. The third or fourth month we find the results with a persuflación and / or hysterosalpingography control. The technique is very similar to hysterosalpingography in which replaced the opaque solution chloromycetin, streptomycin and hyaluronidase dissolved in 9 ml. saline, always remembering to be applied at very low pressure.